Nissen fundoplication in Cornelia de Lange syndrome spectrum: Who are the potential candidates?. Issue 7 (21st May 2020) - Parma, Barbara; Cianci, Paola; Mariani, Milena; Cereda, Anna; Panceri, Roberto; Fossati, Chiara; Maestri, Luciano; Macchini, Francesco; Onesimo, Roberta; Zampino, Giuseppe; Betalli, Pietro; Cheli, Maurizio; et al.
Abstract: Cornelia de Lange spectrum (CdLSp) is a rare genetic condition characterized by intellectual disability, facial dysmorphisms, major malformations, growth impairment, and development delay. Approximately 80% of CdLSp patients have gastroesophageal reflux disease (GERD) with a varied clinical presentation. The aim of this study is to define potential clinical/genetic risk factors based on the clinical phenotype description of CdLSp patients with severe GERD who underwent surgical treatment. We retrospectively collected data from 23 CdLSp patients, 13 females and 10 males. Mean age of the patients undergoing surgical treatment was of 4 years. 21/23 (91%) had a molecular characterization, of which 21/21 (100%) had a NIPBL gene mutation, while 2/23 (9%) did not have a genetical characterization, only a clinical diagnosis. Most of our patients presented a moderate–severe severity score (21/23, 91%) with limb malformations evidenced in 10/23 (44%) of our patients and a moderate–severe intellectual disability in 20/23 (87%). Therefore, CdLSp patients harboring NIPBL variants, upper limb malformations and severe psychomotor delay are more likely to suffer from severe GERD, not responsive to proton pump inhibitors treatment. These features should be considered as clinical markers for potentially severe GERD that might require surgical treatment.